El Trienio y sus códigos. Estudios - Petit Calvo, Carlos Manuel (Historia del Derecho, 2022)
The author participated in several scientific initiatives celebrantig the so-called Trienio Liberal (1820-1823). At his colleagues request, his previous experience in the study and edition of the draft Civil Code of 1821 led him to write repeatedly about codification. The result, conveniently arranged, is in the hands of the reader.